A More Corrosion Resistant Hercules? Alloy - A. Muwila (The Southern African Institute of Mining and Metallurgy, 2007)
Hercules? is a low nickel austenitic stainless steel developed at Mintek that has a typical composition of 9 wt% Mn, 0.05 wt% C, 2wt% Ni, 0.25 wt% N and 16.5 wt% Cr. A more corrosion resistant version of Hercules? (Hercules? B) with 0.5 wt% Mo has also been developed. Potentiodynamic tests performed on Hercules? B in a 5wt% sulphuric acid solution showed it to have improved corrosion resistance comparable to that of AISI 304. The effect of a varying Mn content on the corrosion resistance of Hercules? B has also been investigated and the results discussed in this paper. From the corrosion test results, it is clear that decreasing the Mn content of Hercules? B increased the corrosion rate, while increasing it decreased the corrosion rate. Keywords: austenitic stainless steel, % ferrite, molybdenum, manganese, nitrogen, electrochemical corrosion tests, potentio-dynamic scans, microstructure, chemical analysis.